Resource-Backed Loans in Sub-Saharan Africa - Mihalyi, David; Hwang, Jyhjong; Rivetti, Diego; Cust, James (World Bank, Washington, DC, 2022)
This paper investigates the characteristics of resource-backed lending across Sub-Saharan Africa. To shed light on this type of lending, the paper presents new information on 30 resource-backed loans between 2004 and 2018, identified through publicly available information. These loans were concentrated in a few countries, where they represented a sizable fraction of all borrowing and were typically taken by central governments and state-owned enterprises. Although the loan terms are mostly opaque, where data are available, the study finds that such loans are not cheaper than regular loans. The paper highlights opportunities to transparency and offers some suggestions for improving the governance of collateralized borrowings across developing countries.